The relationship between carbon dioxide sensitivity and sprint or endurance performance in young swimmers - McGurk, S. P.; Blanksby, B. A.; Anderson, M. J. (British Journal of Sports Medicine, 1995)
There has been some evidence that extremes of CO2 sensitivity can indicate an individual's potential for sprint or endurance athletic performance. This study examined the responses to CO2 rebreathing, and previously validated sprint and endurance tests by subjects who were involved in regular, but not intensive, swimming training. The aim was to determine whether subjects with low CO2 sensitivity might perform better on endurance tests, whilst those subjects with high CO2 sensitivity would be more successful in the sprint tests. Initially, 168 young (mean mean(s.d.) age = 12.4(2.1) years) swimmers were measured using a modified version of the Read CO2 rebreathing technique. From this sample, 17 high (mean means(s.d.) = 2.24(0.39) 1 min-1 mmHg-1) CO2 responders were matched by gender, age, height, weight and FVC with 17 low (mean means(s.d.) = 0.57(0.19) 1 min-1 mmHg-1) responders. Each of these 17 pairs underwent two sprint tests (10 s Tri-level alactic power, 50 m run) and two endurance tests (PWC170, 1.6 km run) in order to determine whether any differences existed between the two groups and the sprint and endurance parameters. The subjects remained unaware of their results of the rebreathing test throughout testing. A dependent t test was then used to compare the results collected from each group. The low CO2 responders recorded a significantly faster 1.6 km run time, but were not superior on the PWC170 ergometer test, than the high CO2 responders. The high CO2 responding group recorded significantly higher results on the 10 s alactic power test, but not the 50 m sprint run, than the low responders.